The relationship between school climate and students' mathematics achievement gaps in Shanghai China: Evidence from PISA 2012. Issue 3 (2nd July 2020) - Teng, Yuan
ABSTRACT: This study explores the effects of school climate on the disparities in students' mathematics achievement, drawing on data from the Programme for International Student Assessment (PISA) 2012 for Shanghai, China. The results of a two-level linear model and quantile regression indicate that three dimensions of school climate (student–teacher relations, disciplinary climate and students' behaviour) compensate for the effect of family background on students' mathematics performance, and that student–teacher relations and teacher morale can moderate the effect of family background on mathematics achievement for underachieving students and for low-performing schools, respectively. This shows the protective role of school climate in the relationship between family background and students' mathematics performance. School climate has a more significant effect in low- and average-performing schools, and for medium-level students and underachievers, compared with high-performing schools and top students, indicating the potential of school climate in narrowing achievement gaps among schools and students. Furthermore, a negative disciplinary climate is the key factor explaining the under-performance of low-performing schools and underachieving students.